STRAIGHTENING THE BOX CURVE OF A STEEP ARCH - Abdulkasim, Mamazhonovich Khusanboev; Abdullaeva , Donokhon (Educational Research in Universal Sciences, 2023)
This article examines the issues of straightening flat curved lines lying on a plane. To straighten the curve, a box curve of the steep vault was constructed along its width AB and height OS. The box curve of a steep vault consists of four arcs of a circle. To straighten the vault, it was necessary to determine the length of each arc of the circle. The author of the article used the small chord method. As the name itself shows, the method consists in inscribing a broken line into a rectifiable flat curve, the links of which represent small chords of the curve. Thus, straightening and determining the length of box flat curves of steep vaults are used in the construction of bridge arches, entrances to buildings and subways, etc.